The Effect of Project-Based Learning Model and Canva Application on Motivation and Learning Interest of Elementary School Students in Bunaken Subdistrict in Indonesian Language Learning - Denysa Anthonia Caroles; Mersty E. Rindengan; Widdy H.F. Rorimpandey (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Education in the era of globalization and the Industrial Revolution 4.0 requires innovative learning approaches that not only emphasize content mastery but also foster 21st-century skills, such as critical thinking, creativity, collaboration, and communication. However, in practice, students' motivation and interest in learning particularly in Indonesian language subjects remain relatively low due to monotonous and less engaging teaching methods. This study aims to examine the effect of the Project-Based Learning (PjBL) model combined with the use of the Canva application on students' motivation and interest in learning Indonesian in public elementary schools in Bunaken District, Manado City. This research employs a quantitative approach with an experimental design. Data were collected through observation, questionnaires, and documentation, and analyzed using appropriate statistical techniques. The results indicate that the implementation of Project-Based Learning integrated with Canva has a positive and significant effect on students' motivation and learning interest. Students become more actively involved, creative, and enthusiastic in participating in the learning process. Additionally, the use of Canva as a visual learning medium enhances students' ability to express ideas and produce meaningful learning outputs. In conclusion, the integration of Project-Based Learning and digital media such as Canva can create more engaging, meaningful, and student-centered learning experiences. This approach is recommended as an innovative strategy for improving the quality of Indonesian language learning in elementary schools, particularly in increasing students' motivation and interest. Keywords: Project-Based Learning, Canva, learning motivation, learning interest, Indonesian language learning.